Exploration of Entrepreneurship Education and Innovative Talent Training Model: New Economic Perspective - Lei, Jianqiang; Hock, Oo Yu; Asif, Mahbub Karim (2021)
In recent years, the network economy marked by e-commerce has developed rapidly, spawned a series of new business models and industrial firms, which have also promoted the development to some extent of the real economy. Especially the outbreak of the Covid-19 pandemic crisis in 2020，internet entrepreneurship through the e-commerce platform and we-media marketing has become the main trend of entrepreneurship under the new normal. This study analyzed the effects of entrepreneurship education (EE) on innovative talent training model, the quantitative data of 400 senior undergraduates from 3 universities in China were collected by questionnaires, the PLS-SEM was adopted to do the proposed data analysis. This study applied the Triple Helix Model of Innovation theory to show the important relevance of government, university, and industry in the innovative development of the new economy. The results showed that the two dimensions of entrepreneurship education: institutional environment and supporting infrastructure have a significant impact on innovative talent training. The findings revealed that the students acquired entrepreneurial capital from university entrepreneurship education programs are very important for the cultivation of innovation capability. and practice-oriented innovative entrepreneurship education should be encouraged to enhance in the new normal economic environment.